Nucleation and bubble growth during puffing and micro-explosions incomposite droplets; Fuel; Vol. 340 - Bar-Kohany Tali; Antonov D. V. Dmitry Vladimirovich; Strizhak P. A. Pavel Alexandrovich; Sazhin S. S. Sergey Stepanovich (2023, 2023)
Title screen